2016
DOI: 10.5812/ircmj.37912
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Monosodium Glutamate and Tannic Acid on Adult Rats

Abstract: BackgroundMonosodium glutamate (MSG) is a widely-used flavor enhancer and stabilizer in ready-made or packaged foods. The excessive use of MSG has been shown to increase oxidative stress in different organ systems and causes glucose metabolism disorders, obesity, and coronary diseases.ObjectivesIn this study, the antioxidant activity of tannic acid was investigated experimentally with respect to its protective effects against overdosed MSG-induced oxidative stress in rats. The study took place in Turkey in Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
2
17
2
3
Order By: Relevance
“…The obtained result was in the same line with [76], who attributed this finding to Graviola's ability to restore body fluids and stimulate erythropoietin [77]. Orally administered MSG led to increased oxidative stress markers, such as MDA, ROS, NO, and H 2 O 2 , and decreased SOD, CAT, GST, and GSH that supported this finding by [9,68,[78][79][80][81] as a result of the exhaustion of SOD and accumulation of H 2 O 2 as a result of ROS formation as a result of MSG. Besides [9], this effect is revealed to MSG lipogenesis characters that consume nicotinamide adenine dinucleotide (NAD) + hydrogen (H) (NADH).…”
Section: Discussionsupporting
confidence: 85%
“…The obtained result was in the same line with [76], who attributed this finding to Graviola's ability to restore body fluids and stimulate erythropoietin [77]. Orally administered MSG led to increased oxidative stress markers, such as MDA, ROS, NO, and H 2 O 2 , and decreased SOD, CAT, GST, and GSH that supported this finding by [9,68,[78][79][80][81] as a result of the exhaustion of SOD and accumulation of H 2 O 2 as a result of ROS formation as a result of MSG. Besides [9], this effect is revealed to MSG lipogenesis characters that consume nicotinamide adenine dinucleotide (NAD) + hydrogen (H) (NADH).…”
Section: Discussionsupporting
confidence: 85%
“…Although MSG was given in very large doses (equivalent to 56 mg was converted to mice's dose compared to our study), but there was not show histopatological changes significantly on the organs. [ 17 ] Interestingly, compared to our study, we had found histological changes in the livers by a dose of 5 mg/20 gBW MSG for 28 days.…”
Section: Discussioncontrasting
confidence: 65%
“…Monosodium glutamate (MSG), also called sodium glutamate, is used as a flavor enhancer in the food industry. MSG gives a flavor that is impossible to achieve with other food additives [ 48 , 49 , 50 , 51 ]. The obtained positive correlations between brain glutamate as an excitatory neurotransmitter and most of the obesity-related markers in the current study can be supported through the recent work of Hernández Bautista et al [ 52 ], in which an MSG-induced obesity model was associated with inflammation and impaired leptin levels.…”
Section: Discussionmentioning
confidence: 99%